MISOGYNIST DI DALAM HADIS (TELAAH HADIS SUNAN TIRMIDZI DAN IBNU MAJAH, PEREMPUAN SUMBER FITNAH PALING BERBAHAYA) - Nurdin Rufika Sari (Marwah: Jurnal Perempuan, Agama dan Jender, 2014)
Today fighter for women’s rights increasingly critical in addressing every thing related to women. As has been known that the more criticism addressed to the traditions of the Prophet, the Prophet is accused of marginalizing the position of women in the presence of men, the Prophet accused of traditions that hatred of women (misogynist). One tradition that really should be dissected is the source of slander women narrated by Imam Nasa’iy and Ibn Majah. Speculation has grown in interpreting these traditions. As if women become mastermind in every error and problems on this earth. Based on this study proved the hadith Tirmidhi and Ibn Majah valid with narrators tsiqah and mutual acceptance and giving history and sanad and can be used as evidence. The purpose of this tradition is the spouse of women for men can be a test or trial for a man, when can be ignored on other obligations